Faith gives fullness to reasoning : the five Theological orations of Gregory Nazianzen - Norris, Frederick W., 1941- (Vigiliae Christianae, Supplements, 1990)
Gregory Nazianzen's Theological Orations , genuine classics, reveal not only the learning and faith of their author, but also his quarrels with Neo-Arians, Pneumatomachians, pagans, and other opponents at Constantinople in the late fourth century C.E. This volume is divided into three parts. The first offers a survey of Gregory's life and works, his orientation as a philosophical rhetorician, an overview of his theology, the relevant views of his major opponents, and the manuscript tradition of these orations. The second is a commentary that concentrates on the context and flow of his arguments about paideia and theology. The third is a new English translation, the first complete one, that evokes the logical and rhetorical power of Nazianzen and through its Biblical citations shows the importance of scripture in the debates.